2011
DOI: 10.3357/asem.3090.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Incidence in U.S. Air Force Aviators Compared with Non-Aviators

Abstract: Introduction Several studies investigating whether prostate cancer incidence is elevated in aviators both in the civilian and military sectors have yielded inconsistent findings. Most investigations have compared aviators to the general population. Instead, our study compared prostate cancer incidence rates among officer aviator and non-aviators in the United States Air Force to reduce confounding by socioeconomic status and frequency of medical exams. Methods This retrospective analysis ascertained prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Second, annual and retirement physical examinations (93% of DoD servicemen retire by the age of 50 years) are mandatory for all personnel, and this heightened vigilance probably increases PSA screening and disease detection, compared with screening in the general population. Our earlier study argued against the possibility that this elevated prostate cancer rate resulted from occupational factors. Third, the argument that financial considerations and medicolegal issues bias physicians toward aggressive management of even very‐low‐risk disease is not pertinent to the Armed Forces, in which there is no case‐volume reimbursement, and litigation by servicemen is prohibited.…”
Section: Introductionmentioning
confidence: 93%
“…Second, annual and retirement physical examinations (93% of DoD servicemen retire by the age of 50 years) are mandatory for all personnel, and this heightened vigilance probably increases PSA screening and disease detection, compared with screening in the general population. Our earlier study argued against the possibility that this elevated prostate cancer rate resulted from occupational factors. Third, the argument that financial considerations and medicolegal issues bias physicians toward aggressive management of even very‐low‐risk disease is not pertinent to the Armed Forces, in which there is no case‐volume reimbursement, and litigation by servicemen is prohibited.…”
Section: Introductionmentioning
confidence: 93%
“…The association seen in the former study disappeared after adjustment for socioeconomic status; similar adjustment was not performed in the latter study. A study evaluating prostate cancer incidence in the active duty U.S. Air Force population from 1987 through 2008 found no difference between aviators and non-aviators [27]. A large study of male active duty U.S. Air Force officers from 1975 through 1989 (officers followed an average of 7.1 years), which relied entirely on hospitalization records (apparently not confirmed by chart review), found that aviators had higher rates of all cancers combined, testicular cancer, and bladder cancer, compared to non-flying officers.…”
Section: Discussionmentioning
confidence: 99%
“…First, each featured a relatively small number of cases. The largest cancer-specific sample size was 73 cases of prostate cancer 7 ; most cancer counts were in the single digits. Second, they had variable inclusion criteria regarding airframe type and seat position, such as combining fixed-wing and rotary-wing airframes or restricting to pilots proper, thus complicating generalizability.…”
mentioning
confidence: 99%